Spatial variation of geometry, binding, and electronic properties in the moiré superstructure of MoS2 on Au(111). (26th January 2022) - Silva, Caio C; Dombrowski, Daniela; Atodiresei, Nicolae; Jolie, Wouter; Farwick zum Hagen, Ferdinand; Cai, Jiaqi; Ryan, Paul T P; Thakur, Pardeep K; Caciuc, Vasile; Blügel, Stefan; Duncan, David A; Michely, Thomas; et al.
Abstract: The lattice mismatch between a monolayer of MoS2 and its Au(111) substrate induces a moiré superstructure. The local variation of the registry between sulfur and gold atoms at the interface leads to a periodic pattern of strongly and weakly interacting regions. In consequence, also the electronic bands show a spatial variation. We use scanning tunneling microscopy and spectroscopy (STM/STS), x-ray photoelectron spectroscopy (XPS) and x-ray standing wave (XSW) for a determination of the geometric and electronic structure. The experimental results are corroborated by density functional theory. We obtain the geometric structure of the supercell with high precision, identify the fraction of interfacial atoms that are strongly interacting with the substrate, and analyze the variation of the electronic structure in dependence of the location within the moiré unit cell and the nature of the band.